2015
DOI: 10.1007/s11071-015-2214-y
|View full text |Cite
|
Sign up to set email alerts
|

Lyapunov method for nonlinear fractional differential systems with delay

Abstract: This paper deals with the stability of nonlinear fractional differential systems with delay. Based on the Lyapunov functional method and the Lyapunov function method, respectively, several stability criteria including Razumikhin-type stability criteria are derived, which are extensions of some existed results of the Hale and Verduyn Lunel (Introduction to functional differential equations. Springer, Berlin, 1993), Aguila-Camacho et al. (Commun Nonlinear Sci Numer Simul 19, 2951-2957 and Zhou et al. (Appl Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 29 publications
(42 reference statements)
0
28
0
Order By: Relevance
“…Lemma (Razumikhin‐type stability) Assume that u,v,w:R+R+ are continuous nondecreasing functions, u ( s ) and v ( s ) are positive for s >0, and u (0)= v (0)=0, and q >1. If there exists a continuous function Vfalse(t,xfalse(tfalse)false):R+×Rndouble-struckR such that (i) ufalse(false‖xfalse‖false)Vfalse(t,xfalse)vfalse(false‖xfalse‖false),tR+,xRn and (ii) D α V ( t , x ( t ))≤− w (‖ x ( t )‖) if V ( t + s , x ( t + s ))< q V ( t , x ( t )),∀ s ∈[−τ,0], t ≥0, then the zero solution of system is asymptotically stable. The following theorem provides a sufficient condition guaranteeing that system is asymptotically stable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemma (Razumikhin‐type stability) Assume that u,v,w:R+R+ are continuous nondecreasing functions, u ( s ) and v ( s ) are positive for s >0, and u (0)= v (0)=0, and q >1. If there exists a continuous function Vfalse(t,xfalse(tfalse)false):R+×Rndouble-struckR such that (i) ufalse(false‖xfalse‖false)Vfalse(t,xfalse)vfalse(false‖xfalse‖false),tR+,xRn and (ii) D α V ( t , x ( t ))≤− w (‖ x ( t )‖) if V ( t + s , x ( t + s ))< q V ( t , x ( t )),∀ s ∈[−τ,0], t ≥0, then the zero solution of system is asymptotically stable. The following theorem provides a sufficient condition guaranteeing that system is asymptotically stable.…”
Section: Resultsmentioning
confidence: 99%
“…Various results on fractional‐order systems have been reported. () It was found that a variety of physical and biological systems can be well characterized by fractional‐order differential equations, such as the fractional‐order Schrodinger equation in quantum mechanics and fractional‐order oscillator in damping vibration. () Fractional calculus offers more advantages than integer‐order calculus.…”
Section: Introductionmentioning
confidence: 99%
“…□ Remark 5 For the case A=0, similar stability conditions were given in [12–14] by using singular value decomposition of the characteristic equations. Moreover, it is worth noting that the asymptotic stability of the LFDDEs (1) can be verified by the Lyapunov stability theorem (Theorem 4.1 in [19] or Theorem 4 in [22]) using Lyapunov function method. However, the solution leads to solving LMIs depending either on the trace of the system matrices or on the positive definite matrix solution, which is not easy to solve and to verify the Lyapunov stability conditions (see, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, if any Lyapunov functional is applied to the system (e.g. by Theorem 4.1 in [19] or by Theorem 4 in [22]), then the stability condition leads to an LMI of the form ][AP+PAnormalT+qPBPPBnormalTI<0where q>1,P is a symmetric positive definite matrix. By the Schur complement lemma, this LMI implies AnormalTP+PA<0, and hence by the Lyapunov equation stability theorem, matrix A is Hurwitz.…”
Section: Resultsmentioning
confidence: 99%
“…In the following, for simplicity, we use a notation D α instead of C 0 D α t . Lemma 2 (Razumikhin-type stability Wen et al 2015) Assume that u, v, w : R + −→ R + are continuous nondecreasing functions, u(s), v(s) are positive for s > 0, and u(0) = v(0) = 0, and q > 1. If there exists a continuous function V (t, x(t)…”
Section: Problem Statement and Preliminariesmentioning
confidence: 99%